2021
DOI: 10.3390/cancers13020239
|View full text |Cite
|
Sign up to set email alerts
|

ADCC against MICA/B Is Mediated against Differentiated Oral and Pancreatic and Not Stem-Like/Poorly Differentiated Tumors by the NK Cells; Loss in Cancer Patients due to Down-Modulation of CD16 Receptor

Abstract: Tumor cells are known to upregulate major histocompatibility complex-class I chain related proteins A and B (MICA/B) expression under stress conditions or due to radiation exposure. However, it is not clear whether there are specific stages of cellular maturation in which these ligands are upregulated or whether the natural killer (NK) cells differentially target these tumors in direct cytotoxicity or antibody-dependent cell cytotoxicity (ADCC). We used freshly isolated primary and osteoclast (OCs)-expanded NK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 73 publications
1
21
0
1
Order By: Relevance
“…As previously described, NK cells play important roles in differentiating CSCs, leading to slower tumor growth, and decreased tumor metastasis [ 26 , 46 ]. Therefore, we cocultured autologous and allogeneic NK and monocytes and used their supernatants to differentiate OSCSCs.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…As previously described, NK cells play important roles in differentiating CSCs, leading to slower tumor growth, and decreased tumor metastasis [ 26 , 46 ]. Therefore, we cocultured autologous and allogeneic NK and monocytes and used their supernatants to differentiate OSCSCs.…”
Section: Resultsmentioning
confidence: 96%
“…Although the defect can be seen in most in-vitro treatments tested including those triggered by IL-2 or the combinations of IL-2 with anti-CD16 mAbs, or IL-2 with anti-CD3/28 mAbs or IL-2 with sAJ2 in PBMCs, the most significant defect was seen in those treated with IL-2 and anti-CD16 mAbs, and the least in those treated with IL-2 and sAJ2. Since we previously observed decreased expression of CD16 on patient NK cells [ 46 ] and significant differences in the function of PBMCs when they were activated with IL-2 and anti-CD16 mAbs, we undertook studies to understand the underlying mechanisms of the insufficient NK cell activation by anti-CD16 mAbs. We purified peripheral blood NK cells and studied their functions following cocultures with autologous and allogeneic monocytes obtained from cancer patient and those of the healthy individuals in the presence of IL-2 and anti-CD16 mAbs activation and compared the effect to those activated with IL-2 and sAJ2.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been suggested that CD16 down-regulation prevents NK cells from overactivation and exhaustion [ 57 ]. Still, lower baseline levels of CD16 correlate with decreased ADCC responses in NK cells: compared with NK cells obtained from healthy donors, it was demonstrated that NK cells from cancer patients showed a significant reduction of both direct killing and ADCC against tumors, which was due to CD16 down-regulation [ 58 ]. In cancer patients, the expression levels of CD16, DNAM-1, and NKG2D have also been reported down-regulation on NK cells [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…The clinical infusion of NK cells or its predecessors, lymphokine-activated killer cells, to treat metastatic tumors is a popular therapeutic direction (50,58,59). In a previous study, the NK-92 cell line was modified with a chimeric antigen receptor specific for PD-L1, ER-retained IL-2 and CD16 (60); in the study, preclinical data showed that these NK-92 cells could kill 15 tumor cell lines in vitro.…”
Section: Clinical Infusion Of Nk Cells In Pancreatic Cancermentioning
confidence: 99%